IMPLEMENTASI QRIS SEBAGAI METODE KEUANGAN DIGITAL DALAM BUDAYA LITERASI KEUANGAN DI WILAYAH PERBATASAN PADA UMKM DI KABUPATEN BENGKAYANG: IMPLEMENTASI QRIS SEBAGAI METODE KEUANGAN DIGITAL DALAM BUDAYA LITERASI KEUANGAN DI WILAYAH PERBATASAN PADA UMKM DI KABUPATEN BENGKAYANG - Regita Ariani; Jones Parlindungan Nadapdap (Jurnal Pengabdian Bukit Pengharapan, 2023)
In the current era of globalization, technological developments are increasing rapidly, including technological developments in the banking world. Where the Indonesian government encourages the banking world to apply financial service technology so that it is easily used by Indonesian people. One of the financial services recently developed by the banking world is QRIS. In the Bengkayang Regency area, the use of QRIS is still very minimal because MSMEs in Bengkayang Regency refuse to use QRIS as their payment method. According to them, the existence of QRIS will make it difficult for customers to pay for their merchandise. This community service program uses an approach in the form of training to increase the understanding and skills of MSME actors regarding the use of financial technology and digital marketing/promotion using social media. The approach to increasing digital marketing/promotion understanding and skills is carried out by holding training on the use of social media, especially Instagram, so that it can make it easier for partners to convey information and documentation of activities in the form of text, images and videos to the wider community.